EFFECT OF BUD FORCING AND ROOT PRUNING ON THE GROWTH OF DAISY MANDARIN BUDDED ON ROUGH LEMON - Jagjeet Singh Dhaliwal; Dr Amarjit kaur (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
In an experimental trial carried out in 2020-2021 at the nursery of Khalsa College Amritsar four forcing methods (Bending, lopping, notching and cutting off) and root pruning were evaluated to access their effectiveness on Daisy mandarin (Citrus sinensis (L.) Osbeck) budded on rough lemon (Citrus jambhiri) rootstock in the field conditions. As a result of the study bending proved to be the superior to other methods in producing outstanding bud growth and increased the scion length, girth, leaves, leaf area, roots and whole plant dry weight. Root pruning reduced bud break, scion growth, scion leaves, root growth and dry weight of the scion and roots. Bud break, sprouting and survival were also significantly better for cutting–off treatment than others under study. Hence there was an immense advantage of bending forcing method in forcing scion bud growth for propagating Daisy mandarin on rough lemon rootstock